Using DNA barcoding to identify host-parasite interactions between cryptic species of goby (Coryphopterus: Gobiidae, Perciformes) and parasitic copepods (Pharodes tortugensis: Chondracanthidae, Cyclopoida) - Forrester, Graham E.; Mccaffrey, Malachy T.; Terpis, Kristina X.; Lane, Christopher E. (Zootaxa, 2021)
Previous work, using morphological characters, identified a generalist copepod parasite (Pharodes tortugensis) at high prevalence on two common gobies (Coryphopterus glaucofraenum and C. dicrus) in the British Virgin Islands (BVI). DNA barcoding subsequently revealed C. glaucofraenum to be three morphologically similar species (C. glaucofraenum, C. venezuelae and C. tortugae), casting doubt on host identities in the BVI and the classification of the parasite as a single species. Mitochondrial cytochrome c oxidase subunit I (COI) data from 67 gobies in the BVI showed that, in addition to C. dicrus, host gobies were a mix of C. glaucofraenum and C. venezuelae, while C. tortugae was unexpectedly absent from the study area. COI data (n = 70) indicated that the copepod infecting all three hosts was a single species, almost certainly P. tortugensis. The pharodes-coryphopterus interaction has a strong impact on host dynamics in the BVI, and a revised understanding of these dynamics must account for any differences among the three newly confirmed hosts in transmission of, and susceptibility to, the shared parasite. No other infected hosts were discovered at our sites, but P. tortugensis is reportedly widespread and infects 12 additional host species elsewhere. Further DNA barcoding is thus needed to test whether P. tortugensis is truly a widespread generalist, or instead represents a group of more specialized cryptic species.